Lonely places, dangerous ground : Nicholas Ray in American cinema - Rybin, Steven, 1979-; Scheibel, Will, 1983- (Albany : State University of New York Press, 2014)
"Examines the director's place in the history of Hollywood and the institution of cinema"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Ray, Nicholas, -- 1911-1979 -- Criticism and interpretation; Motion picture producers and directors -- United States; Electronic books